Platelet Count Recovery after Endovascular Aneurysm Repair for Abdominal Aortic Aneurysm - Inoue, Kentaro (Ann Vasc Dis, 2021)
Objective: To find a new predictor of endoleak (EL) and aneurysm sac expansion after endovascular aneurysm repair (EVAR), we evaluated the platelet count recovery (PCR) process after EVAR. Materials and Methods: Two hundred five patients treated with elective EVAR from 2007 to 2015 were retrospectively analyzed. We compared the platelet count ratio until postoperative day (POD) 7 to the presurgical baseline between patients with and without persistent EL (≥ 6 months). Subsequently, we calculated the optimal platelet count ratio for distinguishing persistent EL using receiver-operating characteristics analysis. A platelet count ratio on POD7 ≥118% was defined as the PCR. We evaluated the PCR’s influence on the cumulative aneurysm sac expansion rate. Results: The average platelet count ratio on POD7 rose above baseline (112%), and the ratio was attenuated by persistent EL (103%). Of 205 patients, 126 (61%) were assigned to the disturbed PCR group (PCR(−) group). Cumulative aneurysm sac expansion rate was higher in the PCR(−) group than the PCR(+) group (34.4% vs. 12.8% in 5 years, p=0.01). Conclusion: Disturbed PCR after EVAR may be associated with ELs and eventual aneurysm sac expansion.